Política educacional do Município de Boa Vista-RR: contribuição do ProJovem urbano para o desenvolvimento local - Vale, Joseane Viana do (2016)
This study aims to analyze the educational policy of the city of Boa Vista-RR: ProJovem Urban's contribution to local development in the context of its links with the national education policy in the light of local development concept. Thus, it was used as a research method survey records by the Municipal Department of Education and Culture (SMEC). We sought to examine the theoretical framework on the concepts of educational policy and local development as an analytical basis elements of the municipal reality of Boa Vista in its relations with the federation. There has been research on the implementation of the National Youth Inclusion Programme: education, training and community action - Urban ProJovem, examining the city's relations with the federal government. For greater understanding, yet sought to, assess the results of the Urban ProJovem in Boa Vista preceded by discussion in the light of local development concept. Complementing, we present a proposal on the quality of teaching in educational institutions.